Elaboración de un manual de tributación básica para contribuyentes del régimen simplificado para emprendedores y negocios populares - RIMPE del casco urbano del cantón Gualaceo, provincia del Azuay - Muycela Guncay, Edita Victoria (2023)
The present Graduation Project was carried out prior to obtaining the Bachelor's Degree in Accounting and Auditing, in accordance with the Academic Regime Regulation of the National University of Loja. The main objective was to provide a practical and accessible manual for entrepreneurs and popular businesses, in order to assist them in complying with the tax regulations applicable to the Simplified Regime for Entrepreneurs and Popular Businesses - RIMPE, which came into effect on January 1, 2022 and has faced difficulties in its implementation due to the reforms introduced throughout the fiscal year. In this context, the delivery of a basic tax manual for the taxpayers of this regime, expressed in a simple and concrete language, describing the applicable formal obligations, but above all, built with the active participation of the taxpayers of this regime, becomes essential. To achieve this, a sample was determined from the patent tax database as of December 2021, provided by the revenue department of the Municipal GAD of Gualaceo Canton. Techniques such as interviews and observations were used to gather information about the real level of knowledge regarding RIMPE, which served as the basis for constructing the proposed manual. Finally, the manual was socialized with the participants in order to make adjustments prior to the final delivery. The investigative work revealed a lack of knowledge primarily regarding the compliance with tax returns, issuance of sales receipts, and recording of income and expenses by the taxpayers. These aspects were addressed clearly and exemplified in the tax manual, fulfilling the objective of providing a support material that is practical and applicable for the taxpayers. Keywords: RIMPE - Entrepreneur - Popular business - Tax reforms